The use of open data from social media for the creation of 3D georeferenced modeling - Themistocleous, Kyriacos (My University, 2016)
There is a great deal of open source video on the internet that is posted by users on social media sites. With the release of low-cost unmanned aerial vehicles, many hobbyists are uploading videos from different locations, especially in remote areas. Using open source data that is available on the internet, this study utilized structure to motion (SfM) as a range imaging technique to estimate 3 dimensional landscape features from 2 dimensional image sequences subtracted from video, applied image distortion correction and geo-referencing. This type of documentation may be necessary for cultural heritage sites that are inaccessible or documentation is difficult, where we can access video from Unmanned Aerial Vehicles (UAV). These 3D models can be viewed using Google Earth, create orthoimage, drawings and create digital terrain modeling for cultural heritage and archaeological purposes in remote or inaccessible areas.
Keywords: Archaeology; Cultural heritage; Photogrammetry; Remote sensing; SfM; UAVs